Effect of chitosan and acid solution coordination steeping time on physiochemical properties and GABA content of germinated brown rice flour produced from brown rice (Oryza sativa L.cv.105) - kongwan, Surathanan; Jangchud, Kamolwan; Jangchud, Anuvat (Asia-Pacific Journal of Science and Technology, 2017)
This research was conducted to determine the effect of solution and steeping time on physical and chemical properties of germinated brown rice flour (Oryza sativaL. cv. 105). The 5x4 full factorial in CRD was conducted: 5 levels of solution (Reverse osmosis water, Citrate buffer pH3, Chitosan/citrate pH3, Citrate buffer pH5 and Chitosan/ citrate pH5) and 4 levels of steeping time (12, 24, 36 and 48 h). The non germinated brown rice was serves as a control. The result showed that moisture content ranged from 5.35-7.29%. Free GABA content, peak viscosity and set back of flour produced from brown rice soaked in chitosan/citrate pH5 were higher than those from soaked in citrate buffer pH3 and chitosan/citrate pH3. For all studied soaking solutions, as steeping time increased, peak viscosity, set back from trough decreased but reducing sugar and free GABA content increased.